Breaking the Waste Cycle: How Central Mindanao University Cut Waste from 30 Tons to 2 Tons - Cecilia Ortiz Bucayong; Rolito G. Eballe; Bienvenido M. Butanas; Ann K. Maniego; Rubie Andoy Arroyo; Domingo P. Lodevico; Ronley C. Canatoy; Julie Ann Asari Orobia; Jocelyn P. Saniel (Universitas Diponegoro, 2025)
This study examines the effective waste management program at Central Mindanao University (CMU), which dramatically reduced its monthly waste generation from 30 tons to just 2 tons. The implementation of key strategies such as the Ban on Single-Use Plastics and the Color-Coded Sacks Policies, integrated into a broader framework aligned with sustainable development goals (SDGs), was crucial for this reduction. As the university transitioned back to in-person classes post-COVID-19, the campus population increased significantly from approximately 11,000 to 17,000, intensifying waste management challenges. In response, CMU established the Office of Environmental and Safety Management (OESM), which effectively tackled these issues by instituting structured policies that not only drastically reduced waste but also enhanced sustainability practices across the campus. The program's success was further amplified by robust community engagement and collaboration with local government, illustrating that a culture of environmental consciousness can effectively meet immediate waste management needs even in the absence of advanced technology. The study highlights how strategic planning and cooperative efforts can lead to significant environmental improvements, positioning CMU’s program as a benchmark for eco-conscious management. It aligns with global zero-waste best practices and demonstrates significant impacts on environmental, social, and governance (ESG) standards.